Aging effects in adrenal cortex of male Mongolian gerbil: A model for endocrine studies - Zucão, Mariele Ilario [UNESP]; Grigio, Vitor [UNESP]; Guerra, Luiz Henrique Alves [UNESP]; Antoniassi, Julia Quilles; Castro, Nayara Fernanda da Costa [UNESP]; Taboga, Sebastião Roberto [UNESP]; Vilamaior, Patricia Simone Leite [UNESP] (Elsevier, 2024)
The adrenal gland produces steroid hormones that act in the homeostasis of organisms. During aging, alterations in the hormonal balance affect the adrenal glands, but these have not yet been fully described due to the lack of adequate animal models. The adrenal gland of the Mongolian gerbil has a morphology similar to the primate's adrenal gland, which makes it a possible animal model for endocrine studies. Therefore, the current study aimed to study the morphophysiology of the adrenal gland under the effect of aging. For this purpose, males Meriones unguiculatus, aged three, six, nine, twelve, and fifteen months were used. Morphometric, immunohistochemical, and hormonal analyses were performed. It was observed that during aging the adrenal gland presents hypertrophy of the fasciculata and reticularis zones. Lipofuscin accumulation was observed during aging, in addition to changes in proliferation, cell death, and cell receptors. The analyses also showed that the gerbil presents steroidogenic enzymes and the production of steroid hormones, such as DHEA, like that found in humans. The data provide the first comprehensive assessment of the morphophysiology of the Mongolian gerbil adrenal cortex during aging, indicating that this species is a possible experimental model for studies of the adrenal gland and aging.
Keywords: Andropause; Dehydroepiandrosterone; Experimental model; Senescence; Steroid hormones